Perceiving the Past: From Age Value to Pastness. Issue 4 (14th December 2017) - Holtorf, Cornelius
Abstract: According to the Austrian art historian Alois Riegl (1857–1905), cultural heritage possesses age value ( Alterswert ) based on the perception of an object's visible traces of age. His 1903 essay "The Modern Cult of Monuments" became a classic, and age value has ever since been constitutive for cultural heritage. Closer scrutiny, however, reveals that clever copies, reconstructions, and imaginative inventions can possess age value too. I therefore suggest "pastness" as a useful term for denoting the perception that a given object is "of the past." Pastness is not immanent in an object but, rather, results from its appearance (for example, patina), its context (for example, in a museum), or its correspondence with preconceived expectations among the audience. In this article, I review the concept of pastness and discuss its implications for the global heritage sector. Age value emerges as being less universal than Riegl thought and was linked to a very particular intellectual and cultural context.